Pharmacokinetic Differences of Wuji Pill Components in Normal and Chronic Visceral Hypersensitivity Irritable Bowel Syndrome Rats Attributable to Changes in Tight Junction and Transporters - Gong, Zipeng; Yang, Qing; Wang, Yajie; Weng, Xiaogang; Li, Yujie; Dong, Yu; Zhu, Xiaoxin; Chen, Ying (Frontiers in Pharmacology, 2022)
The Wuji pill, also called Wuji Wan (WJW), is an effective traditional medicine for the clinical treatment of irritable bowel syndrome (IBS). It is principally composed of Rhizoma Coptidis, Fructus Evodiae Rutaecarpae, and Radix Paeoniae Alba. There have been no reports on the pharmacokinetics of WJW on IBS. Because it is more meaningful to study pharmacokinetics in relation to specific pathological conditions, our study investigated the pharmacokinetic differences of five representative components (berberine, palmatine, evodiamine, rutaecarpine, and paeoniflorin) in normal rats and chronic visceral hypersensitivity IBS (CVH-IBS) model rats after single dose and multiple doses of WJW using ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). Transmission electron microscopy, immunohistochemistry, and immunofluorescence were used to explore mechanisms behind the pharmacokinetic differences in terms of tight junction proteins (Occludin and ZO-1), myosin light chain kinase (MLCK), and transporters including P-glycoprotein (P-gp), multidrug resistance associated protein 1(MRP1), and multidrug resistance associated protein 2(MRP2) in rat colons. After a single dose, for all components except rutaecarpine, significant differences were observed between normal and model groups. Compared with normal group, T1/2 and AUC0-t of berberine and palmatine in model group increased significantly(562.5 ± 237.2 vs 1384.9 ± 712.4 min, 733.8 ± 67.4 vs 1532.4 ± 612.7 min; 5443.0 ±1405.8 vs 9930.8±2304.5 min.ng/mL, 2365.5 ± 410.6 vs 3527.0 ±717.8 min.ng/mL ), while Cl/F decreased( 840.7±250.8 vs 397.3 ±142.7 L/h/kg, 427.7 ±89.4 vs 288.9 ±114.4 L/h/kg). Cmax and AUC0-t of evodiamine in model group increased significantly(1.4± 0.6 vs 2.4± 0.7 ng/mL ; 573± 45.3 vs 733.9±160.2 min.ng/mL ), while T1/2, Tmax, Cl/F and Vd/F had no significant difference. Tmax and AUC0-t of paeoniflorin in model group increased significantly( 21.0± 8.2 vs 80.0 ± 45.8 min ; 15428.9±5063.6 vs 33140.6 ± 5613.9 min.ng/mL), while Cl/F decreased( 110.5± 48.1 vs 43.3± 9.5 L/h/kg ). However, after multiple doses, all five components showed significant differences between normal and model groups. Moreover, these differences were related to tight junction damage and the differential expression of transporters in the colon, suggesting that dose adjustment might be required during administration of WJW in the clinical treatment of IBS.